Immunogenic cell stress and death in the treatment of cancer - Pan, Hui; Liu, Peng; Zhao, Liwei; Pan, Yuhong; Mao, Misha; Kroemer, Guido; Kepp, Oliver (Seminars in cell & developmental biology, 2024)
The successful treatment of oncological malignancies which results in long-term disease control or the complete eradication of cancerous cells necessitates the onset of adaptive immune responses targeting tumor-specific antigens. Such desirable anticancer immunity can be triggered via the induction of immunogenic cell death (ICD) of cancer cells, thus converting malignant cells into an in situ vaccine that elicits T cell mediated adaptive immune responses and establishes durable immunological memory. The exploration of ICD for cancer treatment has been subject to extensive research. However, functional heterogeneity among ICD activating therapies in many cases requires specific co-medications to achieve full-blown efficacy. Here, we described the hallmarks of ICD and classify ICD activators into three distinct functional categories namely, according to their mode of action: (i) ICD inducers, which increase the immunogenicity of malignant cells, (ii) ICD sensitizers, which prime cellular circuitries for ICD induction by conventional cytotoxic agents, and (iii) ICD enhancers, which improve the perception of ICD signals by antigen presenting dendritic cells. Altogether, ICD induction, sensitization and enhancement offer the possibility to convert well-established conventional anticancer therapies into immunotherapeutic approaches that activate T cell-mediated anticancer immunity.